Pembaruan Pemikiran Islam di Indonesia antara Psikologi Kolonial dan Keharusan Historis - Yusdani Yusdani (Universitas Islam Indonesia, 2009)
The following article tries to investigate the plurality and dinamicity of Islamic thought intwentieth century in Indonesia from the positive effect of muslim education in history. Theeducation in this sense, is modern education - university. The characteristics of universitygraduation is mastering the methodology. The mastering methodology influences towardhow to understand or intepret Islam in term of the reality of Indonesia. Because of this,there are several differences of islamic thought that emerge in Indonesia.The classificationof Indonesian Islamic thought can be classified into exlusive Islamic thought, inclusiveIslamic thought, pluralistic Islamic thought, humanist Islamic thought, etc. The positiveimpact of pluralities in Islamic thought that appearing in Indonesia is preparing manychoices for muslim in Indonesia especially in term of how to response the challenging oflife, either in the field of politics, economics, culture or that of other sphere of life.Keywords: Indonesia, pemikiran, Islam, pendidikan, dan metodologi